Front Cover: Theoretical and Experimental Investigations of Stable Arylfluorene‐Based Radical‐Type Mechanophores (Chem. Eur. J. 12/2023). Issue 12 (3rd February 2023) - Sugita, Hajime; Lu, Yi; Aoki, Daisuke; Otsuka, Hideyuki; Mikami, Koichiro
Abstract : A human dive into the ocean of α‐SOMO levels : Exhaled oxygen bubbles cause peroxidation of radical‐type mechanophores (RMs), which generate shallow α‐SOMO level radical species; however, RMs that generate deep α‐SOMO level radical species did not afford peroxide compounds. One of the C−C RMs was applied to the design of a mechanoresponsive polymer. More information can be found in the Research Article by H. Otsuka, K. Mikami, and co‐workers. (DOI: 10.1002/chem.202203249 ).